Magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosive coating as well as preparation method and application thereof

Through the modified potassium magnesium phosphate-based steel anticorrosion coating of magnesium borate whiskers, the problems of short service life and poor durability of steel anticorrosion coating in the prior art are solved, and the coating with high toughness and excellent corrosion resistance is achieved, which significantly improves the corrosion resistance of steel.

CN119552525APending Publication Date: 2025-03-04JIANGSU UNIV OF SCI & TECH

Patent Information

Application Number
CN202411291223.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing steel anti-corrosion coatings have problems such as short service life, poor durability, complex processes, and environmental pollution, making it difficult to effectively prevent steel corrosion.

Method used

A highly tough and corrosion-resistant anticorrosion coating is used to modify the potassium magnesium phosphate-based steel anticorrosion coating by gelling potassium magnesium phosphate, borax and magnesium borate whiskers in a specific proportion to form a highly tough and corrosion-resistant anticorrosion coating.

Benefits of technology

It significantly increases the service life and durability of the coating, provides excellent corrosion resistance, reduces the corrosion driving force of the steel, and improves the toughness and compressive resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552525A_ABST
    Figure CN119552525A_ABST
Patent Text Reader

Abstract

The invention discloses a borate whisker modified magnesium potassium phosphate based steel anticorrosive coating and a preparation method and application thereof, and the anticorrosive coating comprises the following substances in parts by weight: 88-95 parts of magnesium potassium phosphate gel, 4-9 parts of borax and 1-3 parts of borate whisker. The potassium magnesium phosphate gel comprises an acid component and an alkali component, and the mass ratio of the acid component to the alkali component to the borate whisker is 1: (2-3). The preparation method comprises the following steps: crushing borax crystals into powder, adding water into the powder and an acid component gelatinized by potassium magnesium phosphate to form a mixed solution, and fully mixing borate whiskers with an alkali component to form mixed powder; and mixing the mixed solution with the mixed powder, and uniformly stirring to obtain the borate whisker modified potassium magnesium phosphate based steel anticorrosive coating. After the magnesium potassium phosphate gel, the borax and the magnesium borate whisker are added, the toughness of an original material is greatly improved, the service life of the material is greatly prolonged, the durability of the material is greatly improved, and an obtained coating is good in corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating and a preparation method and application thereof, and specifically to a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating and a preparation method and application thereof. Background Art

[0002] Steel itself has the characteristics of high strength and light weight, but it is easily corroded in the natural environment, which changes the surface state of the steel and significantly reduces the mechanical properties. Every year, there are countless safety accidents caused by structural failure due to steel corrosion around the world. The cost and difficulty of repairing and replacing steel parts are high, requiring a lot of manpower and material resources. The steel lost due to corrosion each year accounts for more than 50% of the total loss.

[0003] At present, the common methods for steel corrosion protection are: (1) applying an anti-corrosion coating on the surface of steel; (2) cathodic protection; (3) using the material itself to resist corrosion. Applying an anti-corrosion coating on the surface of steel is a common and efficient anti-corrosion method. Common anti-corrosion coatings are divided into metal, organic or inorganic coatings. Metal coatings require complex processes such as electroplating, chemical plating, and thermal spraying. A large amount of strong acid, strong alkali solution, and toxic and harmful chemicals are required during the coating formation process. It also produces heavy metal wastewater and waste materials that seriously pollute the environment. Organic coatings volatilize toxic and harmful gases during the curing process. The expansion coefficient of organic coatings is greatly different from that of the metal substrate, and they are prone to cracking and peeling. Ordinary magnesium phosphate cement also has good corrosion resistance, but due to its high brittleness and low toughness, it will show signs of peeling after being attached to the steel surface for a long time. Summary of the invention

[0004] Purpose of the invention: In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating with long service life and good durability. Another purpose of the present invention is to provide a simple and convenient preparation method of the magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating. Another purpose of the present invention is to provide an application of a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating in steel corrosion protection.

[0005] Technical solution: The magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating described in the present invention comprises the following substances in parts by weight: 88 to 95 parts of potassium magnesium phosphate gel, 4 to 9 parts of borax, and 1 to 3 parts of magnesium borate whiskers.

[0006] Further, potassium magnesium phosphate gelling includes an acid component and an alkali component, and the mass ratio of the acid component to the alkali component and the magnesium borate whisker is 1:2 to 3. Preferably, the mass ratio of the acid component to the alkali component and the magnesium borate whisker is 1:2.5.

[0007] Furthermore, the acid component is potassium dihydrogen phosphate, and the base component is dead-burned magnesium oxide.

[0008] Furthermore, the average particle size of the dead-burned magnesium oxide is 25 to 35 μm.

[0009] Furthermore, the average particle size of potassium dihydrogen phosphate is 245 to 350 μm.

[0010] Furthermore, the average particle size of borax is 180-250 μm, and borax is used as a component for regulating the setting time.

[0011] Furthermore, the diameter of the magnesium borate whisker is 0.5 to 20 nm, and the length is 10 to 50 μm.

[0012] The method for preparing the magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating comprises the following steps:

[0013] Step 1, crushing borax crystals into powder, adding water to the acid component gelled with potassium magnesium phosphate to form a mixed solution, and then fully mixing the magnesium borate whiskers with the alkali component to form a mixed powder;

[0014] Step 2: Mix the mixed solution with the mixed powder, stir evenly, and obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating.

[0015] Furthermore, the mass ratio of the acid component to water in the mixed solution is 7 to 8:1, and the mass ratio of the alkali component to water in the mixed powder is 12 to 16:1.

[0016] Application of the above-mentioned magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating in steel corrosion protection.

[0017] Working principle: There are two different theories about the reaction mechanism of MPC: sol-gel and solution-diffusion. The sol-gel theory believes that magnesium oxide and potassium dihydrogen phosphate are first dissolved in water to form Mg(OH)2 hydrosol and KH2PO4 hydrosol. The two types of hydrosols are mixed with each other and then undergo acid-base neutralization reaction to generate a gel, which in turn promotes the formation of more hydrosols. Finally, the crystal nuclei of the reaction products continue to grow, contact and intergrow with each other, and the gel is saturated and crystallized to form a crystalline structure network with unhydrated magnesium oxide particles as the skeleton and phosphate crystallization reaction products as the binder.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0019] 1. After adding potassium magnesium phosphate gel, borax, and magnesium borate whiskers, the toughness of the original material is greatly increased, and its service life and durability are greatly increased;

[0020] 2. From the polarization curve, it can be seen that the corrosion potential is almost unchanged and has been at a higher potential, which means that during the immersion process, the corrosion driving force of the steel substrate in the 3.5% NaCl solution has not changed. The coating provides excellent corrosion protection for the steel substrate throughout the immersion cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a polarization curve diagram of the anti-corrosion coating obtained in Example 1 of the present invention;

[0022] Figure 2 is a polarization curve diagram of the anti-corrosion coating obtained in Example 2 of the present invention;

[0023] Figure 3 is a polarization curve diagram of the anti-corrosion coating obtained in Example 3 of the present invention;

[0024] Figure 4 This is the polarization curve of the coating obtained in Comparative Example 1;

[0025] Figure 5 is a SEM image of the anti-corrosion coating obtained in Example 1 of the present invention;

[0026] Figure 6 This is the SEM image of the coating obtained in Comparative Example 1. DETAILED DESCRIPTION

[0027] In the following examples, the average particle size of dead burned magnesium oxide (magnesia) is 25-35 μm, and the specific surface area is 1489 m 2 / kg, purity ≥88.15%, purchased from Nanjing Wanhui Chemical Industry Co., Ltd., model purity ≥99%. The average particle size of potassium dihydrogen phosphate is 245-350μm, purity ≥99%. Borax crystals were purchased from Xilong Science Co., Ltd., purity ≥99.5%.

[0028] Example 1

[0029] A method for preparing a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating comprises the following steps:

[0030] (1) 9 parts of borax crystals are crushed into powder with an average particle size of 200-260 μm, and mixed with 25 parts of potassium dihydrogen phosphate, an acid component of potassium magnesium phosphate gel, and 6 parts of water to form a mixed solution, and then 3 parts of magnesium borate whiskers and 63 parts of alkali component dead-burned magnesium oxide are fully mixed at room temperature to form a mixed powder. The diameter of the magnesium borate whiskers is 0.5-20 nm and the length is 10-50 μm.

[0031] (2) The mixed solution obtained in step (1) is mixed with the mixed powder at room temperature, and stirred at 180 r / min for 2 min to obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating, which is recorded as MBW-3.

[0032] Application Example 1

[0033] The magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating obtained in Example 1 is used for steel corrosion protection. The specific steps are: spraying the anti-corrosion coating obtained in Example 1 with a thickness of 800 μm on the surface of 400mm×400mm×2mm Q235 steel, and then curing and standing for 300 minutes in an environment of 20±3℃ and 90%RH.

[0034] Example 2

[0035] A method for preparing a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating comprises the following steps:

[0036] (1) 7 parts of borax crystals are crushed into powder with an average particle size of 200-260 μm, and mixed with 26 parts of potassium dihydrogen phosphate, an acid component of potassium magnesium phosphate gel, and 7 parts of water to form a mixed solution, and then 2 parts of magnesium borate whiskers and 65 parts of alkali component dead-burned magnesium oxide are fully mixed at room temperature to form a mixed powder. The diameter of the magnesium borate whiskers is 15 nm and the length is 30 μm.

[0037] (2) The mixed solution obtained in step (1) is mixed with the mixed powder at room temperature, and stirred at 180 r / min for 2 min to obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating, which is recorded as MBW-2.

[0038] Example 3

[0039] A method for preparing a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating comprises the following steps:

[0040] (1) 4 parts of borax crystals are crushed into powder with an average particle size of 200-260 μm, and mixed with 27 parts of potassium phosphate and magnesium phosphate gelled acid component potassium dihydrogen phosphate or ammonium dihydrogen phosphate and 6 parts of water to form a mixed solution, and then 1 part of magnesium borate whisker is fully mixed with 68 parts of alkali component dead-burned magnesium oxide at room temperature to form a mixed powder. The diameter of the magnesium borate whisker is 15 nm and the length is 30 μm.

[0041] (2) The mixed solution obtained in step (1) is mixed with the mixed powder at room temperature, and stirred at 180 r / min for 2 min to obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating, which is recorded as MBW-1.

[0042] Example 4

[0043] A method for preparing a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating comprises the following steps:

[0044] (1) 8 parts of borax crystals are crushed into powder with an average particle size of 200 μm, and mixed with 26 parts of potassium magnesium phosphate gelled acid component ammonium dihydrogen phosphate and 5 parts of water to form a mixed solution, and then 3 parts of magnesium borate whiskers and 63 parts of alkali component dead-burned magnesium oxide are fully mixed at room temperature to form a mixed powder. The diameter of the magnesium borate whiskers is 0.5 nm and the length is 10 μm.

[0045] (2) The mixed solution obtained in step (1) is mixed with the mixed powder at room temperature, and stirred at 180 r / min for 2 min to obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating.

[0046] Example 5

[0047] A method for preparing a magnesium borate whisker modified potassium magnesium phosphate-based steel anticorrosion coating comprises the following steps:

[0048] (1) 5 parts of borax crystals are crushed into powder with an average particle size of 260 μm, and mixed with 26 parts of potassium magnesium phosphate gelled acid component ammonium dihydrogen phosphate and 6 parts of water to form a mixed solution, and then 3 parts of magnesium borate whiskers and 66 parts of alkali component dead-burned magnesium oxide are fully mixed at room temperature to form a mixed powder. The diameter of the magnesium borate whiskers is 20 nm and the length is 50 μm.

[0049] (2) The mixed solution obtained in step (1) is mixed with the mixed powder at room temperature, and stirred at 180 r / min for 2 min to obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating.

[0050] Comparative Example 1

[0051] The remaining steps of this comparative example are the same as those of Example 1, with the only difference being that the borate whiskers are omitted and an equal amount of dead-burned magnesium oxide is added, i.e., 0 parts of borax crystals and 72 parts of dead-burned magnesium oxide are replaced in step (1), and the prepared slurry is recorded as MBW-0.

[0052] Comparative Example 2

[0053] The remaining steps of this comparative example are the same as those of Example 1, except that 5 parts of borate whiskers are added. It was found that the material hardened too quickly and could not be added effectively.

[0054] The coatings obtained in Examples 1 to 3 and Comparative Example 1 were sprayed on the steel surface according to the method of Application Example 1, and test blocks of 40 mm × 40 mm × 200 mm were made in the order of standard numbers MBW-0, MBW-1, MBW-2, and MBW-3, and the flexural strength was tested on a pressure testing machine. It can be seen from Table 1 that with the increase of fiber content, the flexural strength of each group of test blocks gradually increased. When the fiber content was cured for 28 days, the maximum flexural strength of MBW was 12.0 MPa, which was 39.5% higher than that of Comparative Example 1. At the same time, during the experiment, the failure form of MKPC (potassium magnesium phosphate cement) changed from the initial brittle failure to obvious ductile failure, and the plastic deformation capacity of the material was significantly improved. The experimental data of the compressive performance of the coating material are shown in Table 2. The compressive test results show that the addition of whiskers does not significantly improve the compressive strength of the MKPC mortar. However, after curing for 28 days, the compressive strength of the MKPC mortar with the addition of MBW is increased by about 20%. This is because MBW has a higher elastic modulus, which improves the compressive strength of MKPC.

[0055] Table 1 Flexural performance data of coating materials

[0056] serial number 7d flexural strength / MPa Strength improvement rate / % 28d flexural strength / MPa Strength improvement rate / % KB 5.8 0 8.6 0 MBW-1 6.2 6.9 10.4 20.9 MBW-2 6.9 19.0 11.5 33.7 MBW-3 7.2 24.1 11.9 38.4

[0057] Table 2 Compressive performance data of coating materials

[0058] serial number 7d compressive strength MPa Strength improvement rate% 28d compressive strength MPa Strength improvement rate% KB 32.9 0 51.1 0 MBW-1 45.2 37.4 50.1 -2.0 MBW-2 47.7 45.0 51.7 1.2 MBW-3 48.6 47.7 52.5 2.7

[0059] Example 6

[0060] Electrochemical polarization curve test:

[0061] According to the method of Application Example 1, the coatings of Examples 1 to 3 and Comparative Example 1 were sprayed on the surface of the steel material, and after solidification, were immersed in a NaCl solution with a mass concentration of 3.5±0.3%.

[0062] like Figures 1 to 4 After adding 5% MBW, an obvious passivation zone appeared in the polarization curve; while at the same immersion time, only an over-passivation zone existed in the polarization curves of other MBW contents. With the increase of MBW content, the corrosion potential of the coating after immersion changed little. Figure 2 It can be seen that MBW-2 with 10% magnesium borate whiskers has the strongest corrosion resistance and the corrosion potential is basically stable at around -0.6V.

[0063] like Figure 5 The crystals in MBW-3 are packed more tightly, without obvious gaps. It can also be seen from the figure that there are only slight cracks on the surface of the crystals.

[0064] The electrochemical fitting results of the coating materials of Examples 1 to 3 are shown in Table 3. It can be seen from Table 3 that the polarization resistance Rp, the corrosion potential Ecoor 、Corrosion current I coor , the numerical value and changing law of the anode slope Ba of the polarization curve and the cathode slope Bc of the polarization curve.

[0065] Table 3 Coating polarization curve fitting results

[0066]

[0067]

[0068] From the data in Table 3, it can be seen that after adding MBW accounting for 1%, 2%, and 3% of the total gel material, the polarization resistance Rp of the coating during the entire immersion cycle is significantly improved compared with MBW-0. During the immersion process, the remaining MBW in the coating continues to react and hydrate with the water that penetrates into the coating, and the Rp value of the coating continues to increase with the increase of immersion time; when immersed for 28 days, the higher the content of MBW, the higher the corrosion potential E of the coating coor The more positive. The reason why the relevant values ​​of MBW-1 are low in the early stage is that reducing magnesium oxide will reduce the anti-corrosion ability in the early stage; and as time goes by, borates gradually participate in the reaction and improve the anti-corrosion ability. Among them, MBW-3 has the largest Rp value, which is about 113% higher than the blank group, but after 28 days of curing, the Rp value of MBW-3 is lower than that of MBW-10. From the changes in the anode slope Ba value of the polarization curve, it can be found that MBW-3 has the largest anode slope after immersion for 3 days, and the Ba value is 140mV, while the Ba value of CSA-0 for the same immersion time is 134mV, indicating that adding about 15% of magnesium borate whisker coating will have a better inhibitory effect on the anode reaction and make it more corrosion-resistant.

[0069] Depend on Figure 5 It can be observed that a large number of flaky MBW whiskers are distributed on the surface of the MBW-3 coating when not immersed. There are a small number of cracks in the KMgPO4·6H2O crystals, and they mainly exist in the gaps not wrapped by the MBW whiskers, which indicates that the cracks have crack deflection at the MBW whiskers. The KMgPO4·6H2O crystals, the hydration product of the MKPC coating, have good adsorption force with the MBW whiskers. This is because after the MBW whiskers are incorporated into the MKPC coating, the MBW whiskers have good chemical compatibility with the MKPC coating, and their hydration products can be well attached to the whisker surface, so that the hydration product of MKPC KMgPO4·6H2O crystals and MBW whiskers form a good bonding force; after immersion for 28 days, the KMgPO4·6H2O crystals on the coating surface are corroded and disappear, leaving only MBW whiskers on the coating surface, preventing further erosion of the corrosive solution, and still providing effective protection for the internal coating. No crack development phenomenon is found in the figure, which shows that MBW whiskers have a good effect on enhancing the strength, toughness and corrosion resistance of the MKPC coating.

[0070] Among the above embodiments, embodiment 1 is the best embodiment.

Claims

1. A borate whisker modified potassium magnesium phosphate based steel anticorrosion coating, characterized in that: The invention comprises the following substances in parts by weight: 88-95 parts of potassium magnesium phosphate gel, 4-9 parts of borax and 1-3 parts of magnesium borate whisker.

2. The magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 1, characterized in that: The potassium magnesium phosphate gel comprises an acid component and an alkali component, and the mass ratio of the acid component to the alkali component and the magnesium borate whisker is 1:2-3.

3. The magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 2, characterized in that: The acid component is potassium dihydrogen phosphate and ammonium dihydrogen phosphate, and the base component is dead-burned magnesium oxide.

4. The magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 3, characterized in that: The average particle size of the dead-burned magnesium oxide is 25 to 35 μm.

5. The magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 3, characterized in that: The average particle size of the potassium dihydrogen phosphate is 245-350 μm.

6. The magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 1, characterized in that: The average particle size of the borax is 200-260 μm.

7. The magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 1, characterized in that: The magnesium borate whisker has a diameter of 0.5 to 20 nm and a length of 10 to 50 μm.

8. The method for preparing a magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, crushing borax crystals into powder, adding water to the acid component gelled with potassium magnesium phosphate to form a mixed solution, and then fully mixing the magnesium borate whiskers with the alkali component to form a mixed powder; Step 2: Mix the mixed solution with the mixed powder, stir evenly, and obtain a magnesium borate whisker modified potassium magnesium phosphate-based steel anti-corrosion coating.

9. The method for preparing a magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to claim 8, characterized in that: The mass ratio of the acid component to water in the mixed solution is 7-8:1, and the mass ratio of the alkali component to the whisker in the mixed powder is 12-16:

1.

10. Use of a magnesium borate whisker modified potassium magnesium phosphate based steel anticorrosion coating according to any one of claims 1 to 7 in steel anticorrosion.

Citation Information

Patent Citations

  • Aqueous inorganic zinc-enriched coating and preparation method thereof

    CN101735674A

  • Magnesium phosphate base reinforcing steel bar protective coating material and preparation method thereof

    CN106116438A

  • Potassium magnesium phosphate-based steel anticorrosive coating material and preparation method thereof

    CN113149597A

Cited By

  • Anticorrosive coating as well as preparation method and application thereof

    CN120842887A